Talent identification test battery: Australian Football League women`s. - Del Basso, A. (Journal of Australian Strength and Conditioning, 2019)
An evidence-based testing battery is critical to identify athletes best suited physically for Australian female football. The 6 physiological tests include: the static and dynamic vertical jump tests, 30m sprint, reactive and non-reactive 45-degree agility test and the yo-yo intermittent recovery test level 1.